Efeitos de um modulador alostérico negativo do receptor metabotrópico de glutamaco do subtipo 5, na obesidade induzida por dieta e no comportamento de compulsão em camundongos - Tadeu Perdigão Diz Oliveira (2018)
Introduction: According to the World Health Organization (WHO), in 2014, more than 1,9 billion people were overweight and more than 500 million were considered obese. Currently, at least 2,8 million people die each year as a consequence of being overweight or obese. Pharmacotherapy for treating obesity is very restricted and there are few drugs available on the world market. Another alarming fact is the high incidence of serious adverse effect related those drugs. Therefore, there is a need for developing new drugs capable of treating obesity. Objectives: To evaluate the drug VU, a new negative allosteric modulator of the subtype 5 metabotropic receptor 1 (mGluR5), for its capability of treating obesity and to evaluate its effects on animals treated with high fat diet submitted to behavioral tests of anxiety and compulsion. Methodology: In the first stage of the study, mice (C57BL/6) were divided into two large groups; one group was treated with standard chow and the other one with high fat diet. The compound VU at doses of 3 and 7,5 mg/kg was administered to the animals for a period of ten days. During this period, behavioral tests of anxiety and compulsion were performed. In the second stage, parallel tests of binge eating with WTs and KOs (mGluR5) were performed. Results: A reduction in the consumption of high fat diet and weight loss were observed in the animals treated with VU at a dose of 7,5 mg/kg. The result of compulsion test (Marble Burying) showed a reduction of the number of marbles buried after being treated with the drug. However, there were no significant results in the behavioral anxiety test. In binge eating trials, treatment with the drug at doses of 7,5 mg/kg and 15 mg/kg was effective. Conclusions: The results demonstrate the efficacy of VU in reducing food intake and binge eating behavior, as well as reducing body weight in animals treated with high fat diet.